Temporal changes in associations between high temperature and hospitalizations by greenspace: Analysis in the Medicare population in 40 U.S. northeast counties. (November 2021) - Heo, Seulkee; Chen, Chen; Kim, Honghyok; Sabath, Benjamin; Dominici, Francesca; Warren, Joshua L.; Di, Qian; Schwartz, Joel; Bell, Michelle L.
Highlights: Trends in heat-hospitalization associations over time were compared by greenness. Hospitalizations from heat stroke and cardiovascular diseases were examined. Higher overall risks of heat stroke were found in regions with less greenspace. Risks for heat stroke decreased over time in regions with less greenspace. Adaptation to heat-hospitalization associations differed by amount of greenspace. Abstract: Although research indicates health and well-being benefits of greenspace, little is known regarding how greenspace may influence adaptation to health risks from heat, particularly how these risks change over time. Using daily hospitalization rates of Medicare beneficiaries ≥65 years for 2000–2016 in 40 U.S. Northeastern urban counties, we assessed how temperature-related hospitalizations from cardiovascular causes (CVD) and heat stroke (HS) changed over time. We analyzed effect modification of those temporal changes by Enhanced Vegetation Index (EVI), approximating greenspace. We used a two-stage analysis including a generalized additive model and meta-analysis. Results showed that relative risk (RR) (per 1 °C increase in lag0–3 temperature) for temperature-HS hospitalization was higher in counties with the lowest quartile EVI (RR = 2.7, 95% CI: 2.0, 3.4) compared to counties with the highest quartile EVI (RR = 0.40, 95% CI: 0.14, 1.13) in the early part of the study period (2000–2004). RR of HS decreased to 0.88 (95% CI: 0.31, 2.53) in 2013-2016 in counties with the lowest quartile EVI. RR for HS changed over time in counties in the highest quartile EVI, with RRs of 0.4 (95% CI: −0.7, 1.4) in 2000–2004 and 2.4 (95% CI: 1.6, 3.2) in 2013–2016. Findings suggest that adaptation to heat-health associations vary by greenness. Greenspace may help lower risks from heat but such health risks warrant continuous local efforts such as heat-health plans.